Enhancing Unemployment Benefits Delivery Through BPM Solution: A Case Study of Reemployment Services Integration - Sai Kiran Nandipati (North American Journal of Engineering Research, 2022)
In the rapidly evolving economic landscape, the efficient delivery of unemployment benefits has become a crucial public service. This technical paper examines a case study involving the integration of Business Process Management (BPM) solutions to enhance the delivery of unemployment benefits, specifically focusing on reemployment services. By addressing common challenges and implementing a robust BPM solution, the study demonstrates significant improvements in service delivery, customer satisfaction, and operational efficiency. The findings provide valuable insights for governmental agencies and organizations aiming to optimize their unemployment benefits systems through technology integration.